Origin of intrinsic luminescence in oxide crystals containing Bi cations and XO₄(X = P, Mo, W) molecular anionic groups - Hizhnyi, Yu.A. (Functional Materials, 2015)
Intrinsic photoluminescence (PL) of BiPO₄, K₃Bi₅(PO₄)₆, K₂Bi(PO₄)(MoO₄), KBi(MoO₄)₂, K₅Bi(MoO₄)₄, K₂Bi(PO₄)(WO₄) and K₆.₅Bi₂.₅W₄P₆O₃₄ crystals is studied in 2.8-14 eV range of excitation photon energies. The electronic band structures of the crystals are calculated by the Full-Potential Linear Augmented Plane Wave Method. Origin of intrinsic luminescence in studied compounds is analyzed on the ground of obtained experimental and computational results. It is found that PL emission components of BiPO₄,K₃Bi₅(PO₄)₆, K₂Bi(PO₄)(MoO₄) and KBi(MoO₄)₂ in the violet-green spectral region are related to radiative transitions in Bi³⁺ ions. The red PL components of K₂Bi(PO₄)(MoO₄), KBi(MoO₄)₂ and K₅Bi(MoO₄)₄ have MoO₄₂--related origin. The red PL component of K₂Bi(PO₄)(WO₄) luminescence is presumably related to the molybdenum impurities. The intrinsic PL emission band of K₆.₅Bi₂.₅W₄P₆O₃₄ is probably not related to Bi³⁺ ions.